Cognitive Restructuring untuk Mengurangi Kenakalan Peserta Didik MTs - Ahsaniatil Muawanah; Asrowi Asrowi; Agus Tri Susilo (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study aims to examine the effectiveness of cognitive restructuring in reducing juvenile delinquency in MTs students. This research is a quasi-experimental with an experimental design in the form of a Non-Equivalent Control Group Design. The subjects of this study were students, totaling 52 students. Sources of data are students. Data collection techniques in this study used a questionnaire. The data analysis technique used the independent sample t-test formula by comparing the averages of the two groups, namely the experimental group and the control group. The test results on the pretest scores of the experimental group and the control group obtained equivalent results. The test results on the experimental and control groups' post-test scores obtained significant results. Thus there is a difference after the treatment of cognitive restructuring. It shows that there is a significant difference between the control group and the experimental group. With this research, it can be concluded that it effectively reduces student delinquency. Based on these results, it is hoped that it will become a reference for implementing Guidance and Counseling services in helping students concerning cognitive restructuring and juvenile delinquency.Abstrak: Penelitian ini bertujuan untuk menguji keefektifan cognitive restructuring dalam mengurangi kenakalan remaja pada siswa MTs. Penelitian ini merupakan eksperimental semu dengan desain eksperimen berbentuk Non-Equivalent Control Group Design. Subjek penelitian ini adalah peserta didik yang berjumlah 52 peserta didik. Sumber data adalah peserta didik. Teknik pengumpulan data dalam penelitian ini menggunakan angket. Teknik analisis data menggunakan rumus independent sample t-test dengan membandingkan rata-rata dua kelompok yaitu kelompok eksperimen dan kelompok kontrol. Hasil pengujian terhadap skor pretest kelompok eksperimen dan kelompok kontrol diperoleh hasil yang setara. Hasil pengujian terhadap skor posttest kelompok eksperimen dan kelompok kontrol diperoleh hasil signifikan, dengan demikian terdapat perbedaan setelah adanya perlakuan pemberian cognitive restructuring. Hal tersebut menunjukkan bahwa terdapat perbedaan yang signifikan antara kelompok kontrol dan kelompok eksperimen. Dengan adanya penelitian ini, dapat disimpulkan bahwa penelitian ini efektif untuk mengurangi kenakalan peserta didik. Berdasarkan hasil tersebut,diharapkan menjadi acuan pelaksanaan layanan Bimbingan dan Konseling dalam membantu peserta didik berkaitan dengan cognitive restructuring dan kenakalan remaja